Crisis management, destination recovery and sustainability tourism at a crossroads - Hassan, Azizul; Kennell, James; Mohanty, Priyakrushna; Sharma, Anukrati 1981- (New York Routledge, 2023)
"The COVID-19 pandemic brought travel to a halt and the global tourism industry has been one of the sectors hit hardest during the pandemic. This book looks at how the tourism industry could enhance its resilience and prepare for future crises more effectively. The book provides insights into the economic, social, geopolitical and environmental implications of the COVID-19 pandemic on the tourism and hospitality industries and the responses in diverse, international contexts. It highlights key concepts and includes cases with real life applications. The book also discusses future research directions in a post-pandemic scenario. This book will be an invaluable resource for practitioners in the areas of tourism and crisis management and for readers to compare and contrast tourism destination recovery and crisis management practices through different research methodologies and settings"--
Introduction: Tourism at a Crossroads -- Section 1. Key Concepts. Tourism at a Crossroads - Ignoring, Adopting, or Embracing Alternative Pathways for More Sustainable Post-Pandemic Tourism Development -- Crisis Management: Managing tourism in the face of adversity -- Destination Recovery: Recovery of the post-pandemic tourism destination economy -- Sustainability and Destination Recovery: Alternatives to overcome the crossroads of the pandemic crisis -- Section 2. Case Studies. Inducing Domestic Tourism through Stokvels in South Africa: Post- COVID-19 Tourism Recovery in the Global South -- Innovative Marketing Strategies During Tourism Recovery in the Post-COVID-19 Period in Nigeria -- The COVID-19 Pandemic and Risk Analysis in Tourism Destinations: Insights from Queen of Hills 'Mussoorie' -- Searching for a Break from the Drudgery of Daily Din: Analyzing Millennials' Quest for Spirituality and Well-being during the Covid-19 Pandemic -- Turkey's Tourism Recovery Process during COVID-19: Policy, Planning and Management -- Restore, reorient, and reinvigorate: A localisation and sensemaking approach to crisis recovery -- Building trust among tourists in the post COVID-19 period: The role of external quality certifications -- Judging the Resilience of Online Learning for Hospitality Courses During COVID-19 -- The Use of Food Delivery Applications in the Restaurant Industry During the COVID-19 Crisis: Consumers' Perspectives -- The COVID-19 Pandemic and (Re)considerations of Occupational Stress in New York City's Hospitality Industry -- Community-based Tourism as a post COVID-19 development strategy in agricultural communities -- Recovery of hotel occupancy using risk management of supply chains in the COVID-19 Pandemic Context at the US-Mexico border -- Virtual tourism and digital communication in the context of the post-pandemic scenario -- COVID-19 and Changing Realities in the Food & Beverage Sector: Exhibiting the Indian Chefs' Perspective.
Includes bibliographical references and index.
Keywords: Crisis management; Emergency management; Sustainable tourism; COVID-19 Pandemic, 2020-2023 -- Influence; Hospitality industry -- Management -- Case studies; Tourism -- Management -- Case studies; Case studies